Violación al Principio Constitucional de Presunción de Inocencia por la no práctica del examen de alcoholemia en el cantón Latacunga - Veintimilla Veintimilla, Henry Paul (2023)
Given the refusal to take the breathalyzer test, it becomes necessary to look into the legal factors that a judge must consider when making his decision and do not judge based on presumptions. Based on the main topic of the discussion, it is necessary to analyze the text of our constitution due to the duties, rights, obligations, and various legal figures, such as the case called PROOF, which must be respected in all procedural instances and the parties that are in a dispute must grant it a correct use without undermining the right of the accused or the victim. It is important to clarify that in all procedural instances, it is necessary to respect the rules of due process since they are the fundamental axis of the guarantees and rights of citizens, the primary need to perform a breathalyzer test is to demonstrate that a person is in a state of drunkenness, to protect the life and property of citizens. This investigation also allows us to interpret the results of all the cases that have been processed and sanctioned for the non-practice of the alcohol test, it should also be noted that the incorrect application of legal norms can cause real violations of Constitutional principles and rights and Because of this, a research and review of the traffic laws' and constitutionals was conducted to protect residents' rights.